2009
DOI: 10.1007/s10765-009-0647-6
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Equilibrium and Critical Phenomena: The Solubilities of Iron(III) Oxide and Cobalt(II,III) Oxide in Isobutyric Acid + Water Near the Consolute Point

Abstract: The solubilities of iron(III) oxide, formula Fe 2 O 3 , and cobalt(II,III) oxide, formula Co 3 O 4 , have been determined in the liquid mixture, isobutyric acid + water, along the critical isopleth at temperatures above the upper critical solution temperature near 299 K. When plotted in van't Hoff form with ln s versus 1/T , the measurements of solubility, s, lie on a straight line for values of the temperature, T , in kelvin, which are sufficiently in excess of the critical solution temperature, T c . The sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…The dissolution of metal oxides by acid/base reaction in IBA/H 2 O produces mixtures having at least six chemical components. We will show that F = 3 in every case where a solubility critical effect has been reported. , Nonetheless, we should not neglect the fact that solubility critical effect can be anticipated even in the absence of reaction, as has recently been demonstrated in the case of the dissolution of excess phenolphthalein in a mixture of nitrobenzene + dodecane . This system consists of three components, and the phase rule calculation shows F = 3 …”
Section: Introductionsupporting
confidence: 51%
See 2 more Smart Citations
“…The dissolution of metal oxides by acid/base reaction in IBA/H 2 O produces mixtures having at least six chemical components. We will show that F = 3 in every case where a solubility critical effect has been reported. , Nonetheless, we should not neglect the fact that solubility critical effect can be anticipated even in the absence of reaction, as has recently been demonstrated in the case of the dissolution of excess phenolphthalein in a mixture of nitrobenzene + dodecane . This system consists of three components, and the phase rule calculation shows F = 3 …”
Section: Introductionsupporting
confidence: 51%
“… a Slope refers to the sign of the critical divergence in the van’t Hoff slope of the measured solubility. b See ref . c See ref . d PF refers to perfluoromethylcyclohexane. e See ref . f See ref . g See ref . h IBA refers to isobutyric acid. i See ref . j See ref . k See ref . l See ref . m See ref . n 2BE refers to 2-butoxyethanol. o The sign refers to the slope of the divergence as determined by the measured concentration of Mn 4+ and not Al 3+ . p The sign refers to the slope of the divergence as measured by the concentration of Al 3+ and not Cu + . q See ref . …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamic property, such as mutual diffusion coefficient, exhibits vanishing as the temperature approaches to critical temperature . The chemical reaction rate exhibits interesting critical behaviors in the liquid–liquid critical binary solutions resulting from critical fluctuation …”
Section: Introductionmentioning
confidence: 99%
“…Snyder and Eckert measured the rate of the Dieles–Alder reaction of isoprene with maleic anhydride in critical binary solutions (binhexane/nitrobenzene, hexane/nitroethane) and found that the reactions accelerated 30–40% near the critical point. Baird et al . investigated the rates of various reactions in different critical binary solutions.…”
Section: Introductionmentioning
confidence: 99%